The Relationship Between the Use of Mobile Social Media and Subjective Well-Being: The Mediating Effect of Boredom Proneness - Bai, Jie; Mo, Kunyu; Peng, Yue; Hao, Wenxuan; Qu, Yuanshan; Lei, Xiuya; Yang, Yang (Frontiers in Psychology, 2021)
Happiness is a hot topic in psychology in recent years. In the network environment, it is of great significance to explore people's subjective well-being.With the increasing use of smart phones, mobile social-media, especially in the form of short video, begins to play an important role in people’s life, and has been associated with the subjective well-being of users. However, the problematic use of mobile social-media also emerges at the same time. This study aims to reveal the relationship between the problematic use of mobile social-media and subjective well-being, and figure out the effect of the Boredom Proneness in mediating the relationship. Therefore, three rating scales were employed to measure the related psychological factors of 656 participants who use mobile applications for sharing short video, including Problematic Mobile Social Media Usage Assessment Questionnaire, Subjective Well-being Scale, and Boredom Proneness Scale. Firstly, significant interactions were found between monthly living expenses and use of mobile social-media, which were recognized as factors affecting subjective well-being. Secondly , there was significant negative correlation between use of mobile social-media and subjective well-being in both the high level and low level of populations, while there was no significantly correlation between the moderate-level groups and subjective well-being. Lastly, it has illustrated that boredom mediates the relationship between mobile social media use and subjective well-being. Our findings indicate that whether the short video can be viewed reasonably directly affects the user's subjective well-being; the use of mobile social media affects the subjective well-being through boredom to a certain extent.